Perception of teachers and students on the use of technology in EFL classes in the ninth grade of the Unidad Educativa Mariscal Sucre : a comparative analysis. - Espinoza Pinzón, Liz Stephanie (2017)
The title of this research project is Perception of teachers and students on the use of technology in EFL classes in the ninth grade of the Unidad Educativa Mariscal Sucre: comparative analysis. The general objective is to compare the perceptions of teachers and students towards the use of technology in the EFL class. The methodological approach relies on constructivism as the philosophical framework and on the case study method with a comparative focus. The research is situated in the U.E. Mariscal Sucre, a private educational institution mainly targeted to middle income households. The target group of study are the 51 girls and the 59 boys of ninth grade and four English teachers. The aspects considered for the qualitative analysis are the surveys for teachers and students and the class observations. The most important conclusions are: students are aware on positive effects of technology, on the barriers their teachers have and on the discipline problems. Also, teacher’s attitudes is not contrary at all, they consider it is relevant to adapt technology. In addition, there is technology available, but there is a need to improve internet access. Lastly, among the similarities, both groups consider that technology is important, know websites to practice English and prefer to work using a projector. Thus, the differences found are that teachers consider as an urgent need to have more training and students regard that electronic media will replace printed text within five years.